Financial Flexibility in Highly Regulated Market: Indonesian Telecommunication Case during Tariff Pricing War - Rijanto, Y. Arief (Universitas Prasetiya Mulya, 2015)
In year 2008, regulation of Indonesian telecommunicationindustries changes due the tariff pricing war within Telecommunication operator. This regulation tie up the telecommunication operator and affect operating revenue margin.The needs of financial flexibility within telecommunication firm is increased.Capex, operating revenue and reinvestment needs to be flexible must be inline with competition and change of technology. This paper goals is measuring financial flexibility based on Capex, operating revenue and re-investment needs.Re-investment needs by Telecommunication operator can be financed with or without financial flexibility. Data from year 2007 up to 2014 is selected to accommodate before and after changes of telecommunication regulation. The regulation effect to financial flexibility of telecommunication firm is still relevantbecause telecommunication industries by nature needs larger capital to re-new the telecommunication technology. Real options method will be used to measure financial flexibility.